2014
DOI: 10.1144/jgs2013-051
|View full text |Cite
|
Sign up to set email alerts
|

Brittle structures focused on subtle crustal heterogeneities: implications for flow in fractured rocks

Abstract: This version is available at https://strathprints.strath.ac.uk/50617/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…This could mean that the corresponding structural changes at shallow depth are initiated by some of the aftershocks. This is consistent with the fact that fluids flow is occurring within a zone of young open fractures probably initiated due to the mechanical contrast between the fault core and the surrounding rock during the earthquake (PYTHAROULLI et al 2011;SODEN et al 2014). The aftershocks can cause new opening cracks (POUPINET et al 1984;SIBSON 1996;BAISH and BOKELMANN 2001) which further can enhance the outward diffusion of pore pressure.…”
Section: Discussionsupporting
confidence: 69%
“…This could mean that the corresponding structural changes at shallow depth are initiated by some of the aftershocks. This is consistent with the fact that fluids flow is occurring within a zone of young open fractures probably initiated due to the mechanical contrast between the fault core and the surrounding rock during the earthquake (PYTHAROULLI et al 2011;SODEN et al 2014). The aftershocks can cause new opening cracks (POUPINET et al 1984;SIBSON 1996;BAISH and BOKELMANN 2001) which further can enhance the outward diffusion of pore pressure.…”
Section: Discussionsupporting
confidence: 69%
“…Damage zones are spatially heterogeneous due to variations in strain around faults at sites of macroscopic fault zone complexity [Childs et al, 2009]. Such variability is also predicted from dynamic rupture models [Johri et al, 2014a] and has been observed in the field [e.g., Zhang et al, 1991;Kim et al, 2003;Soden et al, 2014]. The 1-D geometry of the core does not capture along-fault spatial variability, so we cannot confirm whether the JFAST site is representative of the entire shallow Japan Trench décollement.…”
Section: Discussionmentioning
confidence: 88%
“…The post-rift formations have experienced limited faulting and folding, but the regional fracture network nonetheless has a high intensity (de Graaf et al, 2017). Whereas syn-rift deformation in the region is influenced by preexisting basement faults, these relations seem mostly absent for fracture networks in the younger and shallower Jandaíra Formation (Kirkpatrick et al, 2013;Soden et al, 2014). We collect a multiscale dataset of fracture geometries using an Unmanned Aerial Vehicle (UAV) to image the large outcrops, combined with photogrammetry to construct georeferenced outcrop images.…”
Section: Introductionmentioning
confidence: 99%